710 NEW PROSPECTIVES IN THE USE OF ELECTROCARDIOGRAM IN ANDERSON-FABRY DISEASE ON AND OFF SPECIFIC DISEASE THERAPY: EARLY DIAGNOSIS AND RESPONSE TO THERAPY. (15th December 2022) - Baldassarre, Riccardo; Di Taranto, Raffaello; Barlocco, Fausto; Lillo, Rosa; Re, Federica; Marchi, Giacomo; Parisi, Vanda; Ferrara, Valentina; Di Nicola, Federico; Chiti, Chiara; Blanes, Juan Gimeno; Graziani, Francesca; et al.
Abstract: Background: Anderson Fabry disease (AFD) is a rare X-linked lysosomal storage disorder caused by deficient activity of α-galactosidase A bringing to intracellular accumulation of globotriaosylceramide (Gb3) in affected tissues, including heart. Progressive cardiac involvement has shown to cause electrocardiographic modifications in these patients. Treatment with enzyme replacement therapy (ERT) or chaperone therapy has demonstrated to decrease Gb3 levels in the heart, but little is known about its influence on ECG evolution. Purpose: to gain new insights about ECG evolution in AFD patients on and off specific disease therapy and to assess its potential role in the diagnosis and the follow-up of these patients. Methods: we analysed the ECG evolution of a multicentre study cohort of 170 patients with a diagnosis of AFD (64 males 38%, median age 46±15 years) for a median follow-up of 64±48 months, dividing them into patients off (group A, N=63) and on (group B, N= 107) specific therapy. Results: the two groups did not differ as regard age at baseline (47±14 vs 44±12 years; p=0, 171) but patients off specific disease therapy (group A) showed lower prevalence of male sex [13(21%) vs 51(48%); p=<0, 001], classic phenotype [36(57%) vs 82(77%); p<0, 001)] and lower values of maximal wall thickness [11±3 vs 13±4 mm; p=<0, 0001]. At baseline group A presented more frequently a normal ECG [44(70%) vs 41(38%), p=0, 0001] showing lower prevalence of repolarization anomalies [16(25%) vs 51(48%), p=0, 005] and left ventricular hypertrophy [14(22%) vs 51(48%), p=0, 001]. During follow-up we observed ECG progression in 9 patients in group A (14%), characterized by the development of repolarization anomalies (N=5; 8%), incomplete right bundle branch block (N=4; 6%), shortening of PR interval (N=2; 3%), left ventricular hypertrophy (N=2; 3%), left atrial enlargement (N=2; 3%) and complete right bundle branch block (N=1; 2%). Differently, in group B an ECG evolution was observed in 31 patients (29%) characterized by the development of repolarization anomalies (N=19; 18%), left atrial enlargement (N=12; 12%), complete right bundle branch block (N=8; 8%), left anterior fascicular hemiblock (N=4; 4%) and left ventricular hypertrophy (N=3; 3%).We observed an improvement in ECG features with a regression of repolarization anomalies only in 1 patient off therapy, which could be explained by the presence of transient overload anomalies. We didn't detect any left bundle brunch block among the patients of the two groups. Conclusion: We observed ECG progression despite specific disease therapy in 29% of patients of group B showing a potential role of ECG as a marker of cardiac specific response to therapy in these patients. Differently we detected ECG progression in 14% of patients off specific therapy, which is consistent with their less advanced cardiac involvement (lower prevalence of male sex, classic phenotype and lower maximum wall thickness), suggesting that ECG could be an important tool to detect an initial cardiac involvement in these patients even in absence of hypertrophy. The absence of left bundle branch blocks in the two groups compared with a significant prevalence of complete and incomplete right conduction delay could suggest a prevalent involvement of the right bundle branch in these patients and could represent a red flag for the diagnosis of AFD.